Reconquête du quartier ancien Yaghmouracen d’Oran : documents d’urbanisme et jeux d’acteurs en question - Youcef Kadri; Fadila Kettaf (Cybergeo, 2018)
The question of the re-conquest of the old districts occupies an important place in official rhetoric in Algeria. Since independence in 1962, the Algerian Government has put in place instruments, projects and protective devices for urban space and heritage. However, the historical fabrics are neglected, being manhandled and enduring physical decay, collapse and abandonment. In Oran, several districts of its city core suffer from this situation. The Yaghmouracen (ex-Saint-Pierre) district is a representative example of the limited urban reconquest of the Oran old districts.This paper presents the documents and projects of the district Yaghmouracen and analyses the actors’ relationships involved in the conduct of the projects. The objective is to examine the factors which prevent the effective implementation of a project aiming for its reconquest. The main issue is to reveal the difficulties in inventing urban planning tools able to integrate the approach of an urban project, to reform urbanism practices and to adopt a better reasoned form of governance for the city center renewal.